Respostas

2013-12-26T14:57:58-02:00
A) {3x + y= 22
    { x - y = 2                  x= 2 + y            método de substituição

3x + y = 22 
3. (2 + y) + y = 22 
6 + 3y + y     = 22 
               4y = 22 - 6
               4y = 16 
                 y = 16/4 
                 y = 4
x = 2+ y
x = 2 + 4 
x = 6

b) { 7x - y = -2 
    { x + 5y = 26                x = 26 - 5y     

7x - y = -2
7 (26 - 5y) - y = -2

182 - 35y - y =
 -2
            -36y =  -2 - 182
            -36y = -184 (-1)
             36y = 184
                y = 184/36
                y = 46
x = 26 - 5y
x= 26 - 5.(46) 
x= 26 - 230
x= - 204

c { x + y = 23 
   { x - y = 3                           x = 3 + y 

x + y = 23 
(3 + y) + y = 23 
3+ y + y  = 23 
          2y = 23 - 3
          2y = 20 
           y = 20/ 2 
           y = 10 
x = 3 + y 
x = 3 + 10 
x = 13 


                         espero ter ajudado, bons estudos (:
1 2 1